Potential of Malaysian local bentonite applications in an oil-well cement industry - Samsuri, Ariffin (2000)
This paper presents the results of experimental studies for Malaysian bentonite application in an oil-well cementing as compare to a world-wide commercially used Wyoming bentonite of USA. The experiments include the performance of class-G cement slurry mixed with bentonite according to API Spec 10(1990). Treatments (dry & wet processes) have been conducted for the Malaysian local bentonite to up grade its performance. In additional XRD and XRF techniques and methylene blue tests were also carried out for bentonite samples. Compressive strength tested at atmospheric and reservoir conditions, free water and density tests of cement slurry were also determined. The results of the experiment show that Malaysian local bentonite has very low degree of swelling, therefore the free water increased in the cement slurry, which is higher as compared to Wyoming bentonite. After treatment processes, the free water decreases in the cement slurry with bentonite concentrations increased. The Lahad Datu bentonite gives more slurry density after the treatments. Moreover the addition of Malaysian bentonite to the cement slurry results in significant decrease in the compressive strength.